SÓYLEW SIGNALLARINDAǴI SHAWQIMDI JOQ ETIWDE AYNALAW USILLARIN PAYDALANIW - Mamatov, N.S.; Jalelov, K.M.; Samijonov, B.N.; Samijonov, A.N.; Madaminjonov, A.D. (SCIENCE and SOCIETY, 2023)
The effectiveness of various mirror functions is investigated for denoising speech signals. Denoising can significantly affect performance when choosing a window function, and windowing methods can improve denoising quality when used correctly. This research compares the performance of various window functions, namely Rectangular, Hanning, Hamming, Blackman, and Kaiser windows using Mean Squared Error (MSE) and Signal-to-Noise Ratio (SNR) metrics.